PENERAPAN METODA RESISTIVITY DAN PERSAMAAN ARCHIE UNTUK KAJIAN POTENSI AKUIFER DI PULAU NATUNA - Agus Kuswanto; Teddy W Sudinda (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2001)
Natuna Island will be developed as main center of LNG mining and refineryactivities which will be located in South Cina Sea. As consequences, manyindustries will grow fast in this island, and water consumption will increasedrastically. Therefore, it is important to identify aquifer potentiality. There is manymetode of identificaton. This paper show the application of resistivity combine with Archie’s equation to identify vertical depth and horizontal profile of aquifer. From resistivity we got value of every rock formation whereas use Archie’s equation we interpreted resistivity value of good aquifer.